2014
DOI: 10.3233/jae-140100
|View full text |Cite
|
Sign up to set email alerts
|

On research of time reversal imaging method and structural health monitoring system

Abstract: Structural health monitoring (SHM) technology is a reliable, efficient and economical approach to increase the safety and reduce the maintenance cost of high performance structures. Among the existing SHM methods, piezoelectric transducers (PZTs) array and Lamb wave based SHM methods are sensitive to small damage and studied by many researchers. In this paper, aiming at developing a practical method for on-line localization of damage and impact on aircraft composite structure which can take advantage of time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Qiu et al [13] used the time reversal method to study the identification of impact sources in a finite isotropic plate. For a given force position, it is found that the maximum peak of the reconstructed signal occurs at the impact location.…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al [13] used the time reversal method to study the identification of impact sources in a finite isotropic plate. For a given force position, it is found that the maximum peak of the reconstructed signal occurs at the impact location.…”
Section: Introductionmentioning
confidence: 99%